Harnessing the Potentials of the New Media for Effective Governance in Nigeria: Perception of Netizens in Anambra State, Nigeria - Nkiru Camila Emechebe; Nyerhovwo Muoboghare; Christian Uzoma Igwe; Oke Edward Edherue; Eugenia Chinweokwu Eneome; Kingsley Chukwudubem Ezekwelu (Britain International for Academic Research (BIAR) Publisher, 2025)
The concept of the global village has resulted in the globalised media environment. As a development that has significantly transformed information dissemination and communication, the New Communication Technologies (NCIS), which gave rise to the global village philosophy, is welding great influence in the society today. In journalism practice, health care service, agriculture, industries, environmental service, the influence of the new media is ubiquitous. It is against this background that this study assessed the potentials of the new media for effective governance in Nigeria. This is premised against the background that the citizens deserve to know government policies, activities and programmes. Government, in turn, owes the citizens a duty to carry them along in policy formulation and implementation. The objectives of this paper were to find out the dominant media of communication through which citizens get information about government policies/programmes, and to ascertain the signification influences of the new media in generating the necessary feedback loop for government. The study was anchored on the Bakhtins theory of dialogism and the technological determinism theory. The study adopted a survey research approach and used the netiziens population in Anambra state. A sample size of 362 was determined for study from a population of 89,255 students in Anambra state. Using questionnaire as the research instrument, the data gathered were presented on simple frequency distribution tables, and subsequently analysed. Result obtained from this survey revealed the new media nurture and streamline democratic governance in Nigeria.